DLTS and C(t) transient study of defects induced by neutron radiation in MOS structures of CCD technology - Ahaitouf, Aziz; Bakhtiar, Hazri; Losson, Etienne; Charles, Jean-Pierre (Faculty of Science, UTM, 2003)
The aim of this paper is to study neutron irradiation effects on PMOS capacitors and NMOSFETs transistors. The characterization of induced defects was made by capacitance transients C(t) measurements, DLTS spectroscopy, and optical DLTS (ODLTS). DLTS spectra present three peaks (1, 2, and 3) due to deep levels created in the semiconductor and two peaks (4 and 5) due to minority carrier generation. Levels 1 and 2 are reported in literature and it was suggested that the level 2 may be due to the divacancy. Two other minority carrier traps have been observed on ODLTS spectra after irradiation. This can explain the decrease of the minority carrier generation lifetime observed in capacitance transients measurements.